Album and student teaching practices among Québec teachers: results of primary survey - Lépine, Ph. D., Martin (Ondina - Ondine, 2020)
The skill Appreciate literary works of the Québec Elementary School Training Program is an ideal context for integrating albums and tales into the classroom (MEQ, 2001/MELS, 2006). However, only a few years ago, only one in five primary school teachers reported that they often worked in literary skills (MELS, 2007), and literary works were still not very popular (Giasson and St-Laurent, 1999). Few data, especially in Québec, made possible to know the place of literature in the school, the practices of teachers and the difficulties they encounter when exploiting literary works, including albums and tales (Dezutter and others, 2007). In order to fill part of this lack of recent surveys in this field and to better understand teaching practices and teacher conceptions about the reading/appreciation of literary works, we conducted in the framework of our doctoral research a questionnaire survey for Québec teachers in the three primary cycles (N = 518). We, thus pursued three objectives: 1) to identify and describe the declared teaching practices relating to activities, materials and evaluation; 2) to identify and describe the conceptions of primary school teachers about ministerial prescriptions, reading/appreciation and teaching; 3) to compare these practices and these concepts according to the cycles. The main results show that Québec elementary teachers say that the material used each week for their reading/appreciation teaching is now composed mainly of integral literary works (66.2%) of various forms/genres, mostly narrative (album: 81.3%, novel: 61.2%, tale: 55.3%). For the album and the tale specifically, primary school teachers (97.1%, p = 0.00) report using albums more than their colleagues in the second (78.5%) and third cycle (64.3%); tales are used more often in the first cycle (67.9%, p = 0.00) than in the second (58.3%) and in the third cycle (36.9%), but to a lesser extent than the album. In this article, we present, based on these results, the teaching practices declared around these two literary forms/genres, and this, on a continuum from the first to the third primary cycle. Key words : teaching practices, album, tale, reading/appreciation, Québec